2020
DOI: 10.3390/brainsci10100681
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Profile Assessment of Posture in Children and Adolescents with Autism Spectrum Disorder and Typically Developing Peers

Abstract: A sound postural system requires sensorimotor integration. Evidence suggests that individuals with Autism Spectrum Disorder (ASD) present sensorimotor integration impairments. The Physiological Profile Assessment (PPA) can be used to evaluate postural capacity assessing five physiological subsets (i.e., vision, reaction time, peripheral sensation, lower limb strength, balance); however, no studies applied the PPA in young individuals. Therefore, this study aimed to investigate the PPA in children and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 67 publications
1
21
0
1
Order By: Relevance
“…ASD diagnosis is still clinical; apart from the core signs of autism, for some time a large number of heterogeneous signs of motor development impairment have been reported in infants and children with ASD. Below, we report some of the most relevant of these signs described in the literature during the past few years: delayed motor development; persistent asymmetry when lying on the stomach at 4 months of age; righting from the supine to the prone position moving all the body en bloc not in a corkscrew fashion; abnormal patterns of crawling; walking asymmetry; sequencing instead of superimposition of one movement on the other for example during gait; unusual positions of arms; poor coordination; muscle tone and reflex abnormalities; choreiform movement of extremities; impaired finger-thumb opposition; stereotyped movements of the body, limbs, and fingers, including hand flapping; unusual gait patterns, including walking on tiptoes; poor motor imitation; impairment of postural control [ 1 , 2 , 3 , 4 , 5 , 6 ]. An approximate idea of the prevalence of motor impairment in ASD is given by Ming et al, who in 154 children found: hypotonia in 51% of cases, apraxia in 34%, walking on tiptoes in 19%, and gross motor delay in 9% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASD diagnosis is still clinical; apart from the core signs of autism, for some time a large number of heterogeneous signs of motor development impairment have been reported in infants and children with ASD. Below, we report some of the most relevant of these signs described in the literature during the past few years: delayed motor development; persistent asymmetry when lying on the stomach at 4 months of age; righting from the supine to the prone position moving all the body en bloc not in a corkscrew fashion; abnormal patterns of crawling; walking asymmetry; sequencing instead of superimposition of one movement on the other for example during gait; unusual positions of arms; poor coordination; muscle tone and reflex abnormalities; choreiform movement of extremities; impaired finger-thumb opposition; stereotyped movements of the body, limbs, and fingers, including hand flapping; unusual gait patterns, including walking on tiptoes; poor motor imitation; impairment of postural control [ 1 , 2 , 3 , 4 , 5 , 6 ]. An approximate idea of the prevalence of motor impairment in ASD is given by Ming et al, who in 154 children found: hypotonia in 51% of cases, apraxia in 34%, walking on tiptoes in 19%, and gross motor delay in 9% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorders (ASDs) refer to a group of neurodevelopmental disorders characterized by marked deficits in social communication and social interactions, along with restricted, repetitive behaviors or interests [1]. Among the several early signs of ASD that have been studied [2][3][4], diminished attention toward social information, or impaired social orienting, emerges as the earliest and the most robust [5][6][7]. Social orienting refers to the child's spontaneous attention toward social information [8].…”
Section: Introductionmentioning
confidence: 99%
“…ADOS-2, Autism Diagnostic Observation Schedule, 2nd edition, 2 MSEL, Mullen Scales of Early Learning,3 AE, Age Equivalent score,4 ESDM-AF+, children with more attention to face at baseline receiving early and intensive intervention,5 ESDM-AF-, children with less attention to face at baseline receiving early and intensive intervention,6 CT-AF+, children with more attention to face at baseline receiving community treatment,7 CT-AF-, children with less attention to face at baseline receiving community treatment.…”
mentioning
confidence: 99%
“…Recently, Melo, Ruano, Jorge, Pinto Ribeiro, Oliveira, Azevedo, and Temudo [ 3 ] reported a higher prevalence of motor stereotypies in individuals with ASD and lower Intellective Quotient (IQ), while gender was not associated with its prevalence. Children and adolescents with ASD may also show postural deficits compared to typically developed peers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%